MODIFICATION OF THE BEST DIET (REGULARLY LOW ENERGY BALANCED) FOR OBESITY YOUTH - Retno Wahyuningsih; Joyeti Darni; Meika Purbowati; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background: Obesity is a teenage health problem that needs to be addressed. One of the handling efforts in overcoming excess weight is proper eating/diet settings. Research Methods: This type of research is a quasi-experimental design with a randomized pre-post test control group design. The research subjects used in this study were female adolescents aged 18-20 years with overweight nutritional status. The variables measured were body weight before and after treatment. The data obtained were tested statistically univariate to get an overview of the distribution of research variables and bivariate test to determine the effect of the REST diet on changes in body weight. Research Result: The results showed that the average weight loss in the treatment group was 0.92 kg, and the control group was 0.67 kg. From the results of the Paired-samples T-Test, a significant value of 0.000 (p <0.05) was obtained, which means that there was a substantial difference in the mean weight before and after treatment. Conclusion: The conclusion is that there is a difference in body weight before and after the study, but there is no effect of giving the REST diet on weight loss in obese adolescents.Background: Obesity is a teenage health problem that needs to be addressed. One of the handling efforts in overcoming excess weight is proper eating/diet settings. Research Methods: This type of research is a quasi-experimental design with a randomized pre-post test control group design. The research subjects used in this study were female adolescents aged 18-20 years with overweight nutritional status. The variables measured were body weight before and after treatment. The data obtained were tested statistically univariate to get an overview of the distribution of research variables and bivariate test to determine the effect of the REST diet on changes in body weight. Research Result: The results showed that the average weight loss in the treatment group was 0.92 kg, and the control group was 0.67 kg. From the results of the Paired-samples T-Test, a significant value of 0.000 (p <0.05) was obtained, which means that there was a substantial difference in the mean weight before and after treatment. Conclusion: The conclusion is that there is a difference in body weight before and after the study, but there is no effect of giving the REST diet on weight loss in obese adolescents.